(untitled) (Psychology Travelogs, 2023)
The article deals with theoretical aspects of professional activity of specialists in socionomic profile with internally displaced persons. The authors of the article clarify that the group of socionomic professions includes: psychologist, social educator, social worker, and doctor. The article shows that the solution of psychological, socio-economic, medical, educational, legal and other problems of internally displaced persons is impossible without team interaction of specialists of socionomic specialities. Each specialist of socionomic profile has its own peculiarities of work with internally displaced persons. The areas of work of a social worker with internally displaced persons include: social, social and informational, social and psychological, social and pedagogical, social and legal, medical and social, financial, socio-economic, material and social and labour. The areas of work of a social educator with internally displaced persons include: teaching them adaptation skills and behaviour in a new environment; assistance in providing humanitarian services to improve the quality of their lives; social inspection, which examines the needs of children of these persons. A social educator facilitates the provision of effective humanitarian services to internally displaced persons in order to improve their quality of life. The main areas of professional activity of a psychologist with internally displaced persons are psychological assistance and psychological support, which are carried out in the following forms: individual work; family counselling; life skills training; self-help and mutual support groups; psycho-correctional groups, etc. Psychological support for internally displaced persons includes first aid and training sessions aimed at developing resilience to stress, strengthening the role of positive activities, developing skills to manage psychological reactions, promoting positive thinking and restoring social contacts. The authors of the article consider the study of professional qualities of specialists in socionomic specialties for work with internally displaced persons in the prospects of further research.